Reporte de un caso clínico de Loxosxelismo en una paciente embarazada: Report of a clinical case of Loxosxelism in an embarrassed patient (La U Investiga, 2024)
Loxoscelismo, also known as recluse spider envenomation, refers to the medical condition caused by the bite of spiders belonging to the Loxosceles genus. In this review, the term is used to describe both the local and systemic symptoms induced by these bites, although in the field of toxicology, it may be employed to refer exclusively to systemic symptoms. Scientific literature related to loxoscelism is not extensive due to the lack of documented spider bites, specifically those where the identification of the spider responsible in the vicinity has been confirmed. Reports based on larger case series involving patients diagnosed with loxoscelism reveal that only 7 to 14 percent of cases have confirmed spider bites. In this context, we present the case of a 26-year-old female patient who experienced a spider bite in the posterior region of her right thigh. This bite led to the development of an erythematous blister with a central halo and ecchymosis, which progressed to cutaneous necrosis within a few days. Additionally, the patient had an adverse reaction to the administered antibiotic therapy. The diagnosis was based on clinical findings and the results of a biopsy of the lesion. Ultimately, the patient recovered without manifesting any systemic complications.While it has been investigated in various contexts, there are aspects poorly understood regarding loxoscelism in specific populations, such as pregnant women. Pregnancy involves significant physiological changes in a woman's body, raising questions about how it could impact the body's response to a venomous spider bite and the implications for both the mother and the fetus.
Keywords: Loxocelismo, picadura de araña, arañas, picadura, necrosis.